Nursing-led ultrasound to aid in trans-radial access in cardiac catheterisation: a feasibility study. (March 2020) - Williams, Trent; Condon, Jeremy; Davies, Allan; Brown, Jennifer; Matheson, Lucinda; Warner, Thomas; Savage, Lindsay; Boyle, Andrew; Collins, Nicholas; Inder, Kerry
Background: Trans-radial access is increasingly common for cardiac catheterisation. Benefits include reduced bleeding complications, length of hospital stay and costs. Aims: To determine the feasibility of implementing a nurse-led ultrasound programme to measure radial artery diameter before and after cardiac catheterisation; to determine radial artery occlusion (RAO) rates, risk factors for RAO and predictors of radial artery (RA) diameter. Method: A prospective observational cohort study design for 100 consecutive patients undergoing cardiac catheterisation, using RA access. Pre- and post-procedural RA diameter were measured using ultrasound, by specialist nurses trained to do so. Logistic regression analyses were performed to determine risk factors for RAO and predictors of RA diameter with results reported as odds ratios (OR) and 95% confidence intervals (CI). Results: There were no adverse events, supporting the feasibility of nurse led ultrasound programmes. A 4% ( n  = 4) rate of occlusion was observed. Haemostasis device application time of greater than 190 min was a predictor of RAO (OR 3.12, 95% CI 0.31–31). Male gender and height were predictors for a RA diameter of >2.2 mm. Conclusions: Nurses can lead the assessment of RA occlusion using ultrasound to enhance planning and care, including monitoring compression times to reduce RAO.